Estimation of temporal-spatial changes of land surface temperature due to land cover changes using remote sensing (Case study: Darab plain) - hosein esmaeili; Seyed hossein Mirmousavi (جغرافیا و توسعه, 2021)
Surface temperature is one of the important parts of the climate system that changes in land use and land cover cause its change and intensification. This study aimed to investigate the effect of land cover changes on Spatio-temporal changes in land surface temperature over 30 years using remote sensing and Landsat satellite images in Darab plain. After the required preprocessing on the images, classification maps of different types of land cover in the study area were prepared and the changes that occurred in each class were investigated. According to the studies, the rangeland class had the highest rate of changes and transformations with 72.14%. In the next step, Land surface temperature (LST) maps were extracted using the normalized index in 5 different classes. Among the temperature classes, the moderate temperature class had the largest area during the study period, which is distributed in almost all areas. Findings indicate that the vegetation areas with an average temperature of 29.82 ° C had a lower temperature than other areas without vegetation. In terms of land uses in the study area, the highest surface temperature during 30 years with an average of 38.07 degrees Celsius belongs to the barren land class. Another significant finding of the research is that the average temperature of pastures (32.03) and residential areas (33.37) of the study area during the study period are close to each other.